QUALITY OF DUG WELLS VIEWING FROM RIVER POLLUTION IN TROPODO VILLAGE, KRIAN DISTRICT, SIDOARJO REGENCY IN 2021 - LESTARI, KHOFIFAH; Sulistio, Irwan; Ferizqo, Ferdian Akhmad (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Surabaya, 2021)
Water pollution of dug wells is an environmental problem that can reduce water quality. Factors that affect the quality of dug well water are tofu industrial wastewater and RPH waste disposal in Tropodo Village. If the location of the dug well is lower than the pollutant source and has a distance of <11 meters, it is estimated that the pollutant source flow will seep into the well. So the aim of the researcher is to analyze the quality of dug well water in terms of river pollution. This type of research uses descriptive qualitative with a cross sectional approach. The variables used are water quality physically, chemically and microbiologically. Sampling was done by purposive sampling as many as 6 samples of dug well water and 1 sample of river water. Data analysis uses tabular form and is described based on Government Regulation No. 82 of 2001. Construction of dug wells in Bale Panjang Hamlet, which is <11 meters from river pollution, 83.33% of well-walled wells do not meet the requirements and all conditions of the well floor are 100% not eligible. The 6 dug wells are not equipped with SPAL which allows contamination of the dug well water. There are still 90.20% of dug well water whose physical quality does not meet the requirements, 56.67% of dug well water which has chemical quality does not meet the requirements and 50% of dug well water with microbiological quality does not meet the requirements. It is concluded that the quality of dug well water is influenced by river contamination from tofu industrial waste and RPH waste and is influenced by other factors such as domestic waste and SPAL seepage from dug wells. It is recommended to the relevant agencies to always conduct counseling about the construction of good wells and SPAL and make home visits to measure the quality of clean water.